New strategies for increasing participation of patients from diverse cultural and religious backgrounds in clinical trials (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
Cultural differences between researchers and potential participants in clinical trials could result in communication barriers, which are likely to hinder awareness and pose challenges to the informed consent process. An intercultural communication approach to the informed consent process could facilitate potential participants' understanding; strategies such as the involvement of family members, cultural insiders, cultural mediators during the consent process should be adopted to overcome language and cultural barriers. The article highlights as well barriers related to the interaction between gender and multicultural issues in cross-cultural communication and stresses some culturally-sensitive strategies for the inclusion of pregnant women in clinical research. Consent procedures tailored to local cultural patterns with a focus on the use of new technologies are discussed.
Keywords: Informed consent; intercultural communication; community engagement; gender; ICT